2021
DOI: 10.1111/dth.15223
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous adverse events related to COVID ‐19 vaccines: A cross‐sectional questionnaire‐based study of 867 patients

Abstract: Considering the emergency approval of the Food and Drug Administration for widespread use of coronavirus disease 2019 (COVID-19) vaccines, evaluating potential vaccine-related adverse effects is critical as it will allow physicians to diagnose and manage these complications properly. In this descriptive cross-sectional questionnaire-based study, we evaluated the possible side effects of the COVID-19 vaccine from June 1, 2021 to June 21, 2021. The Iranian population is generally vaccinated with AstraZeneca, Spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 16 publications
6
43
0
5
Order By: Relevance
“…Several cutaneous reactions have been reported after COVID‐19 vaccination such as injection site reaction, exanthematous rash, urticaria, vesicular eruption, chilblain‐like lesions, erythromelalgia, angioedema, erythema multiforme‐like lesion, and zoster. 9 , 11 , 12 , 13 Similar results were found in our local registry. However, our study found a lower incidence of cutaneous adverse reactions affecting only 5% of the population that could either be explained by the separate calculation of injection site reactions including pain, swelling, and redness from other cutaneous reactions or by the fact that there was an actual lower incidence in the Saudi population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several cutaneous reactions have been reported after COVID‐19 vaccination such as injection site reaction, exanthematous rash, urticaria, vesicular eruption, chilblain‐like lesions, erythromelalgia, angioedema, erythema multiforme‐like lesion, and zoster. 9 , 11 , 12 , 13 Similar results were found in our local registry. However, our study found a lower incidence of cutaneous adverse reactions affecting only 5% of the population that could either be explained by the separate calculation of injection site reactions including pain, swelling, and redness from other cutaneous reactions or by the fact that there was an actual lower incidence in the Saudi population.…”
Section: Discussionsupporting
confidence: 89%
“…Several cutaneous reactions have been reported after COVID‐19 vaccination such as injection site reaction, exanthematous rash, urticaria, vesicular eruption, chilblain‐like lesions, erythromelalgia, angioedema, erythema multiforme‐like lesion, and zoster 9,11–13 . Similar results were found in our local registry.…”
Section: Discussionsupporting
confidence: 89%
“…Skin manifestations in the vaccinated subjects were transient. The most common reactions were pain at the injection site (79.9% of Sputnik V (Gam-COVID-Vac) vaccine users, 60.6% of Sinopharm vaccine users), tightening of the injection site (13.4% of Sputnik V (Gam-COVID-Vac) vaccine users, 10.3% of Sinopharm (BBIBP-CorV) vaccine users), reddening of the skin at the injection site (12.8% of Sputnik V (Gam-COVID-Vac) vaccine users, 6.9% of Sinopharm (BBIBP-CorV) vaccine users) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although angioedema is considered a typical manifestation of immediate-type reactions, it can also occur with delayed reactions 6 . Angioedema has been reported after SARS-Cov-2 vaccines 7 )-( 8 , including Covishield, but the underlying pathophysiological mechanism remains unknown. It is important to note that angioedema has also been described as a manifestation of SARS-Cov-2 infection itself 9 )-( 10 .…”
Section: Discussionmentioning
confidence: 99%